20-Hydroxyeicosatetraenoic acid (20-hete) promotes a malignant phenotype in human castration-resistant prostate cancer cells through stimulation of the g protein-coupled receptor gpr75 - Cardenas, Sofia (2019)
20-Hydroxyeicosatetraenoic acid (20- HETE), the product of 20-hydroxylation of arachidonic acid by cytochrome P450 isoforms (CYP4F2 and CYP4A11), has a role in the oncogenesis of several human tumors. Recently, the GPR75 receptor has been identified as the target for 20-HETE. We have shown that androgen independent prostate cancer cells (PC-3) express GPR75. The aim of this study was to assess in vitro if 20-HETE/GPR75 modify the metastatic features of PC-3 cells. Cells were incubated with 20-HETE or its stable analog 5,14- HEDGE (both 0.1 nM) in the presence or absence of two different antagonists of the 20-HETE receptor, AAA or 19-HEDE (both 5 or 10 uM). The following assays were performed: e-cadherin and vimentin protein expression (epithelial-mesenchymal transition), zymography (release of matrix metalloproteinase-2 (MMP-2)), immunofluorescence and p-FAK (changes of cytoskeleton), scratch wound healing (migration), and soft agar colony formation (anchorage-independent growth). Results were analyzed using one-way ANOVA followed by Dunnet’s. 20-HETE (24 h) increased by 150 % the expression of vimentin (p<0.0001, n= 3) and diminished by 40 % the expression of ecadherin (p<0.0001, n= 3), whereas these effects were reversed by AAA (p<0.0001 and p<0.05, respectively). 20-HETE increased by 52 % the release of MMP-2 (p<0.05, n= 3), and this was also inhibited by AAA (p<0.001). AAA disorganized the actin filaments throughout PC-3 cells, while tubulin filaments remained unchanged. Also, 20-HETE increased by 89 % FAK phosphorylation (Y397) (p<0.0001, n= 3). 20-HETE increased by 147 % cell migration rate (p<0.0001, n= 3) and this effect was reverted by both antagonists, AAA or 19-HEDE (p<0.05 and p<0.0001, respectively), or by knockdown of GPR75 (p<0.0001). Finally, 5,14-HEDGE (21 days) formed twice the number of colonies vs. control (p<0.05, n= 2) and this was abolished by AAA (p<0.05). These results strongly suggest a role for GPR75 in 20-HETE-mediated metastatic features in PC-3 cells.